Blood lead levels and bladder cancer among US participants: NHANES 1999–2018 - Mei Huang; Hongxiao Li; Jiahui Chen; Liuqiang Li; Yifei Zhan; Yuxuan Du; Jun Bian; Meiling Chen; Dehui Lai (BMC Public Health)
Abstract Background and objectives Pb (lead) is a heavy metal, its carcinogenicity for bladder cancer is still debated, the link between blood lead levels (BLLs) and bladder cancer was investigated in this study. Methods This cross-sectional study, using the NHANES (1999–2018) database, explored the relationship between BLLs and bladder cancer among Americans aged 20–85. It employed weighted multivariable logistic regression for analysis. Additionally, subgroup analyses and smoothed curve fitting were also performed. Results This study included a total of 40,486 participants, the body mass index (BMI) of the participants is 28.71 ± 6.68 kg/m2. The average BLL is 0.0858 μmol/L (range: 0—2.96 μmol/L). A fully adjusted model showed that the BLL was associated with bladder cancer (odds ratio [OR] = 2.946, 95% confidence interval [CI] = 1.025 to 8.465, P = 0.047) in people with BMI < 28 kg/m2. However, no difference was found in the BMI ≥ 28 kg/m2 subgroup or in the general population. According to the subgroup analysis of participants with a BMI < 28 kg/m2, blood lead was associated with bladder cancer in the male, nonhypertensive, and < 70-year-old subgroups (p < 0.05) but no significantly different is observed in other subgroups. In addition, we discovered a nonlinear association between the BLLs and bladder cancer risk using a linear regression model. Conclusion In this cross-sectional study, we found that the degree of correlation between BLLs and the risk of bladder cancer may vary among people with different BMIs. In people with BMI < 28 kg/m2, a higher BLL was independently associated with bladder cancer. However, more experiments are needed to confirm this finding.